Therapeutic potential of Lycium barbarum-derived exosome-like nanovesicles in combating photodamage and enhancing skin barrier repair - Ye Zhang; Bo Zhao; Jing Wang; Zeyi Zhang; Meiping Shen; Chengjie Ren; Mimi Li; Melanie Liu; Zhicheng You; Ping Li (Extracellular Vesicle)
In this study, the efficacy of Lycium barbarum L.-derived exosome-like nanovesicles (LB-EVs) in reinforcing skin barrier function were evaluated. Using a 3D skin model, expression levels of skin barrier proteins such as filaggrin, loricrin and claudin-1 were found to be modulated favorably upon treatment with LB-EVs, suggesting a role in maintaining cutaneous homeostasis. Additionally, we observed upregulated aquaporin 3 (AQP3) expression and increased natural moisturizing factor (NMF) components, indicating improved skin hydration. A split-face clinical trial involving individuals with sensitive skin revealed that incorporating LB-EVs into a cosmetic serum matrix led to reduced facial redness and transepidermal water loss (TEWL) compared to the control group. Two-photon imaging further demonstrated thickening of the stratum corneum on the treated side after 14 days of application, suggesting enhanced barrier integrity. The findings from this study highlight the potential of LB-EVs to fortify the skin's protective barrier, providing a novel therapeutic strategy for the management of photodamage and the enhancement of skin health.